A Comparative Analysis of Critical Chain and Critical Path Project Management Methods - ALNEHLAWI, SAAD (İstanbul Kültür Üniversitesi, 2022)
PM is practically all procedures that help to reduce the waste of time and resources while most of the planned projects were using much more than what was assigned. These procedures include planning, managing, and monitoring processes of the project from its start to its end, covering the team management, cost optimization, activities scheduling, evaluating, and reporting. Two of the most commonly-used project scheduling methods are the Critical Path Method (CPM) and Critical Chain Project Management (CCPM). This thesis is presenting a comparison between CPM and CCPM showing the pros and cons of both methods when dealing with resource-depending projects. It shows the new features that can be achieved using CCPM, and the reasons that led to its use this new scheduling approach. This study also illustrates the application of both of the techniques in a real case study for an agricultural investment company, to explain how much CCPM can be more reliable and efficient in terms of time-saving and achieving the objectives of this kind of project. It is concluded that CCPM is a more suitable project management planning methodology to apply to this kind of project than CPM.
Kritik Zincir ve Kritik Yol Proje Yönetim Metodlarının Karşılaştırmalı Analizi
▪ Yüksek lisans tezi.
Keywords: Critical Chain Project Management; Project Management; Project Schedulin